2005
DOI: 10.1016/j.ijintrel.2005.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Learning styles and typologies of cultural differences: A theoretical and empirical comparison

Abstract: This study presents the relationship between six typologies of cultural differences and the learning styles of Kolb's learning model. Several cross-cultural studies about learning styles indicate that learning styles may differ from one culture to another, but few studies have addressed the question of which culture is related to which learning style or ability. The present study concerns this inquiry. Exploration of this inquiry has been made in two parts. The first part investigates conceptual analogies and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(105 citation statements)
references
References 30 publications
2
102
0
1
Order By: Relevance
“…However, studies that investigated the relationship between cross-cultural differences and learning styles and learning styles and other background and demographic features have concluded that "cultures do have distinctive learning style patterns and learning styles are a function of both nature and nurture" [126]. Yamazaki [109] and Joy and Kolb [107] studied the relationship between a particular culture and a certain LS by using Kolb's LSI. The results illustrated that each particular culture adopts a certain learning style.…”
Section: Resultsmentioning
confidence: 99%
“…However, studies that investigated the relationship between cross-cultural differences and learning styles and learning styles and other background and demographic features have concluded that "cultures do have distinctive learning style patterns and learning styles are a function of both nature and nurture" [126]. Yamazaki [109] and Joy and Kolb [107] studied the relationship between a particular culture and a certain LS by using Kolb's LSI. The results illustrated that each particular culture adopts a certain learning style.…”
Section: Resultsmentioning
confidence: 99%
“…People with diverging learning styles have strong potential to understand what behaviours are appropriate in different cultural contexts (Phillion, 2002). However, because they are less inclined to take (Pratt, 1991;Yamazaki, 2005). However, whilst diverging and converging learning styles tend to dominate Confucian and Anglo cultures respectively; learning styles can also vary within cultures due to a combination of disposition, personality type, educational specialization, career choice, current job role and tasks (Kolb & Kolb, 2009).…”
Section: Page 8 Of 59 Academy Of Management Learning and Educationmentioning
confidence: 99%
“…Peoples national culture (Yamazaki, 2005;Yamazaki & Kayes, 2004), work environment (Choo, 1998) and individual learning styles (Armstrong & Mahmud, 2008;Kolb & Kolb, 2005) have all been shown to influence the acquisition of tacit knowledge. When peoples learning styles are matched with their work environment, it has been demonstrated that they achieve significantly more learning outcomes in an educational context (Dunn & Griggs, 2003) and higher levels of managerial tacit knowledge in a management context Elaborating further on this person-culture congruence theory, individuals with a strong orientation toward the converging learning style would rather deal with technical tasks and problems than with social and interpersonal issues (Kolb, 1984).…”
Section: Tacit Knowledge In Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…For example culture and learning styles (Yamazaki, 2005); culture and information technology (Johns, Smith & Norman, 2003); personality and information interaction (Heinstrom, 2010); information use and international students (Hughes, 2009(Hughes, , 2013); information use and task complexity (Bystrom & Jarvelin, 1995). In comparison, very little empirical data exists on students' information use related to national culture in the UAE.…”
Section: Purpose and Scopementioning
confidence: 99%